Mitochondrial ATP synthesis activated by exciton energy transfer from Müller cell intermediate filaments - Khmelinskii, Igor (2022)
ATP production by mitochondria isolated from yeast cells (S. cerevisiae) was accelerated by exciton energy transfer from intermediate filaments (IFs). The effect was dependent on mitochondrial concentration and the intensity of light used to generate excitons. Presumably, mitochondrial cytochrome C (CC) was activated by IF exciton energy transfer to CC in the inner mitochondrial membrane (IMM), generating electronically excited CC, and the respective excitation energy was then used in the ATP production chain. A qualitative model was proposed describing observations, although more experiments are required before the detailed mechanisms could be deduced. The present results support the earlier proposed hypothesis of ATP production in vertebrate retina by excess photons in daytime, when retina needs extra energy for recovering the used opsins. Additionally, it shows that at early stages of evolution mitochondria could have been using solar radiation to produce ATP.